Collaborative Governance in the Electronic Road Pricing Implementation Plan in Jakarta - Annisa, Izzah; Sampurna, Agung Firman (Universitas 17 Agustus 1945 Surabaya, 2024)
The proliferation of private vehicle ownership and the associated increase in traffic volume hasprompted the government to introduce an Electronic Road Pricing (ERP) policy to managecongestion and mitigate air pollution in the Special Region of Jakarta (DKI). This study seeks todelve into the application of collaborative governance in the Jakarta ERP policy's execution bygiving prominence to the historical aspects of problem identification, planning review, systemcontext study, dynamic elaboration, collaborative actions, and resulting outcomes, to fulfill thegovernment's objectives for the ERP plan. The research methodology employs a literature reviewand case study, qualitative descriptive methods, and secondary data. The findings reveal acollaborative governance process within the Jakarta ERP policy's implementation, particularlyconcerning system context, collaborative governance regime, collaborative dynamics,collaborative actions, and their associated outcomes. Moreover, based on the study's findings, theDKI Provincial Government is urged to sustain the engagement of community and privatestakeholders in formulating draft regional regulations about electronic traffic control and toenhance the management and governance of transportation infrastructure in Jakarta, all aimedat guaranteeing the inclusiveness, effectiveness, quality, and acceptance of this policy up until itsfuture execution.